2014
DOI: 10.1039/c4cp01444h
|View full text |Cite|
|
Sign up to set email alerts
|

A reduced radial potential energy function for the halogen bond and the hydrogen bond in complexes B⋯XY and B⋯HX, where X and Y are halogen atoms

Abstract: It is shown by considering 76 halogen- and hydrogen-bonded complexes BXY and BHX (where B is a Lewis base N2, CO, C2H2, C2H4, H2S, HCN, H2O, PH3 or NH3 and X, Y are F, Cl, Br or I) that the intermolecular stretching force constants kσ (determined from experimental centrifugal distortion constants via a simple model) and the intermolecular dissociation energies Dσ (calculated at the CCSD(T)(F12*)/cc-pVDZ-F12 level of theory) are related by Dσ = Cσkσ, where Cσ = 1.50(3) × 10(3) m(2) mol(-1). This suggests that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 92 publications
(29 reference statements)
1
58
0
1
Order By: Relevance
“…The full geometries of these complexes are available in the form of the cartesian coordinates in the Supplementary Material. We note from Tables 1 and 2 Tables 1 and 2, that these complexes tend to be more strongly bound according to both criteria (D e and k σ ) than those of a wide range of hydrogen-, halogen-, tetrel-, pnictogen-and chalcogen-bonded complexes with a similar set of Lewis bases previously investigated [20][21][22]. Typically, for the hydrogen-and halogen-bonded complexes considered in [22] Table 2.…”
Section: Molecular Geometriesmentioning
confidence: 80%
See 2 more Smart Citations
“…The full geometries of these complexes are available in the form of the cartesian coordinates in the Supplementary Material. We note from Tables 1 and 2 Tables 1 and 2, that these complexes tend to be more strongly bound according to both criteria (D e and k σ ) than those of a wide range of hydrogen-, halogen-, tetrel-, pnictogen-and chalcogen-bonded complexes with a similar set of Lewis bases previously investigated [20][21][22]. Typically, for the hydrogen-and halogen-bonded complexes considered in [22] Table 2.…”
Section: Molecular Geometriesmentioning
confidence: 80%
“…We note from Tables 1 and 2 Tables 1 and 2, that these complexes tend to be more strongly bound according to both criteria (D e and k σ ) than those of a wide range of hydrogen-, halogen-, tetrel-, pnictogen-and chalcogen-bonded complexes with a similar set of Lewis bases previously investigated [20][21][22]. Typically, for the hydrogen-and halogen-bonded complexes considered in [22] Table 2. It should be noted, from Table 1 and Table 2, that these complexes tend to be more strongly bound according to both criteria (De and kσ) than those of a wide range of hydrogen-, halogen-, tetrel-, pnictogen-and chalcogen-bonded complexes with a similar set of Lewis bases previously investigated [20][21][22].…”
Section: Molecular Geometriesmentioning
confidence: 80%
See 1 more Smart Citation
“…It had been shown that many hydrogen-and halogen-bonded complexes have binding energies directly proportional to the intermolecular stretching force constant and that both could therefore reasonably be described by the Morse potential. 18 The Lennard-Jones 19,20 potential which can be regarded as a special case of the Mie potential, 21 is the common choice for describing intermolecular interactions (such as van der Waals interactions, hydrogen bonding, and halogen bonding). The Lennard-Jones function offers computational advantages over other functions and it has only two adjustable parameters.…”
Section: Potential Energy Functionsmentioning
confidence: 99%
“…Tests of this model showed remarkably small deviations from experiment of less than 0.5 kcal mol −1 in many cases, although unsurprisingly these errors increased upon extrapolation to new systems. More recent work has attempted to extend this approach to other types of non-covalent interaction, including halogen bonds [68,69]. Such a model would be ideal for halogen-bonded systems as it requires minimal effort.…”
Section: Introductionmentioning
confidence: 99%